Креативний податковий облік: методологічні основи уніфікації з фінансовим обліком - Хомин, П. Я. (Видавництво Львівської політехніки, 2014)
Викладено міркування стосовно проблеми методологічного обґрунтування функціонування креативного податкового обліку та його уніфікації з фінансовим обліком. Відзначається недостатня увага вчених до цієї проблеми, що зумовлює паралелізм цих двох підсистем бухгалтерського обліку та непродуктивні витрати, пов’язані з дублюванням відображення доходів і витрат, як і визначення фінансових результатів за приписами фіскального законодавства й П(С)БО. Пропонується власне бачення можливого вирішення проблеми застосування елементів креативності в податковому обліку й уніфікації його з фінансовим. The results of the critical analysis of the unification of financial and tax accounting, identified aspects of the comparability of these types of records. Investigated parity methodological framework set out basic principles of tax accounting standards accounting standards. The article presents considerations concerning the problemofmethodological study of creative functioning taxation and its unification of financial accounting. There is a lack of scholarly attention to this problem , which leads to the parallelism of the two sub- accounting and overhead associated with duplicating reflect income and expenses and determine the financial results for the fiscal requirements of the legislation of the National Accounting Pronouncements. It is proved that the use of creative accounting treatments related transactions lies in the fact that income is no coordination with the increase and decrease in asset commitments may affect the recognition insignificant amount of income, expense is no coordination with the decrease and increase asset committed to commitments, the violation period expensing; overstatement (understatement) cost reporting period, the recognition on transactions, which in its economic essence can not be included in the cost. The conclusion about the unreasonableness of parallel conducting financial and tax accounting types, arguments solving existing problems be based on deep (adaptive) standardization finanсіаl account. Suggested own vision of a possible solution to the problemof the use of elements of creativity in the tax records and unify it with the financial.
Creative tax accounting: methodological foundations unification accounting
Keywords: облік; фінансовий; податковий; креативний; стандартизація; регламентація; законодавство податкове; податки; платежі; податкові зобов’язання; accounting; finance; tax; creative; standardization; regulation; tax laws; tax payments; tax liabilities